67PPooled safety analysis of tepotinib in Asian patients with advanced solid tumours. (24th November 2019) - Yamazaki, K; Ryoo, B-Y; Doi, T; Paik, P K; Veillon, R; Decaens, T; Faivre, S; Falchook, G S; Hong, D S; Scheele, J; Bruns, R; Berghoff, K; et al.
Abstract: Background: Promising clinical activity has been reported in patients with MET-altered NSCLC treated with tepotinib, an oral, selective, potent MET tyrosine kinase inhibitor. To support clinical development, we aimed to further characterize the safety profile of tepotinib in patients with cancer. Methods: In this analysis from 5 phase I and II studies of tepotinib administered 500 mg once daily, adverse events (AEs), graded by NCI CTCAE v4.03, were pooled and summarized for all patients and for the subgroup of Asian patients. Results: As of 28 Sep 2018, 228 patients (81 [35.5%] Asian, 59 [25.9%] NSCLC, 121 [53.1%] HCC) had received tepotinib 500 mg/day for a median of 2.7 months (range 0–21.5); in the ongoing phase II VISION study (NCT02864992), median was 4.1 months. The most common treatment-related AE of any grade was peripheral edema occurring in 33.8% of patients overall and in 24.7% of Asian patients. Other common treatment-related AEs were diarrhea, fatigue, and nausea (Table). Dose reduction due to an AE regardless of causality occurred in 33 (14.5%) patients and discontinuation in 49 (21.5%) patients; peripheral edema led to a dose reduction in 12 (5.3%) patients and discontinuation in 7 (3.1%) patients. In the Asian population, 13 (16.0%) patients had a dose reduction and 13 (16.0%) patients discontinued due to an AE; peripheral edema led to a dose reduction in 4 (4.9%) Asian patients and to no discontinuations. Two AEs leading to death were considered by the investigator to be potentially treatment-related and occurred in patients with HCC (upper gastrointestinal hemorrhage [in an Asian patient] and hypoglycemic coma). Conclusions: Tepotinib demonstrated an acceptable safety profile in patients with advanced cancer, with a similar profile in Asian patients and in the overall population. Further characterization of the clinical relevance of peripheral edema is ongoing. Clinical trial identification: NCT01014936, NCT01832506, NCT01988493, NCT02115373, NCT02864992. Editorial acknowledgement: Medical writing assistance (funded by Merck Healthcare KGaA, Darmstadt, Germany) was provided by Jen Lewis, PhD of Bioscript Science (Macclesfield, UK). Legal entity responsible for the study: Merck KGaA. Funding: Merck KGaA. Disclosure: K. Yamazaki: Honoraria (self): Chugai; Honoraria (self): Takeda; Honoraria (self): Yakult; Honoraria (self): Daiichi‐Sankyo; Honoraria (self): Merck Serono; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Bayer; Honoraria (self): Eli Lilly; Honoraria (self): Taiho; Research grant / Funding (institution): BMS; Research grant / Funding (institution): Sanofi. P.K. Paik: Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: AbbVie; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Celgene; Research grant / Funding (institution), Travel / Accommodation / Expenses: EMD Serono; Honoraria (self): Takeda. R. Veillon: Advisory / Consultancy, Speaker Bureau / Expert testimony: MSD; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Novartis; Speaker Bureau / Expert testimony, Research grant / Funding (institution): BMS; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Roche; Research grant / Funding (institution): Takeda; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Merck. T. Decaens: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: BMS; Honoraria (self), Travel / Accommodation / Expenses: Bayer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Advisory / Consultancy: Ipsen; Honoraria (self), Travel / Accommodation / Expenses: Gilead; Honoraria (self), Travel / Accommodation / Expenses: AbbVie; Honoraria (self): Sanofi; Advisory / Consultancy: BTG; Advisory / Consultancy: Sirtex; Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: MSD; Travel / Accommodation / Expenses: Merck Serono; Research grant / Funding (institution): ArQule; Research grant / Funding (institution): Genoscience Pharma. S. Faivre: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Blueprint; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer Pharma; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Eli Lilly; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Ipsen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Merck Serono; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: MSD; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis. G.S. Falchook: Licensing / Royalties: Wolters Kluwer; Advisory / Consultancy, Travel / Accommodation / Expenses: Fujifilm; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: EMD Serono; Travel / Accommodation / Expenses: Bristol-Myers Squibb; Travel / Accommodation / Expenses: Millennium; Speaker Bureau / Expert testimony: Total Health Conferencing ; Research grant / Funding (institution): 3-V Biosciences; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): ADC Therapeutics; Research grant / Funding (institution): Aileron; Research grant / Funding (institution): American Society of Clinical Oncology; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): ARMO; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): BeiGene; Research grant / Funding (institution): Bioatla; Research grant / Funding (institution): Biothera; Research grant / Funding (institution): Celldex; Research grant / Funding (institution): Celgene; Research grant / Funding (institution): Ciclomed, Curegenix, Curis, DelMar, eFFECTOR, Eli Lilly, Exelixis, Fujifilm, Genmab, GlaxoSmithKline, Hutchison MediPharma, Ignyta, Incyte, Jacobio, Jounce, Kolltan, Loxo, MedImmune, Millennium, Merck, miRNA Therapeutics, National Institutes of Health, No. J. Scheele: Full / Part-time employment: Merck KGaA. R. Bruns: Full / Part-time employment: Merck KGaA. K. Berghoff: Full / Part-time employment: Merck KGaA. All other authors have declared no conflicts of interest.